УЛМАНБЕТ ХОЖАНАЗАРОВ ЛИРИКАСЫНЫҢ ЖАНРЛЫҚ ӨЗГЕШЕЛИКЛЕРИ - Досымбетова, А. (FAN va JAMIYAT, 2025)
The article studies the role of poet U. Khozhanazarov in modern Karakalpak poetry. Genre features of the poet’s lyrics are analyzed. Genre characteristics of love lyrics are studied. Artistic studies in philosophical-meditative lyrics are considered. The poet’s artistic appearances in publicistic lyrics are analyzed.